The manifestation of interlanguage pragmatics in direct and indirect request strategies used by international students - Oktavia, Diana; Batyi, Szilvia; Mukminin, Amirul; Santos, Myla L.; Astrero, Emily T.; Torress, Joel Mayo; Marzulina, Lenny (Universitas Syiah Kuala, 2023)
This study focused on how interlanguage pragmatics (ILP) is manifested in a multicultural environment. Learners ability to make requests has received considerable attention in ILP research because requests are intrinsic face-threatening acts. The question this study aimed to address was to what extent a culture has an impact on the direct and indirect level of request strategies. The data were collected from thirty participants (fifteen males and fifteen females) representing five nationalities (Russian, Indonesian, Pakistani, Jordanian, and Hungarian) and studying at the University of Pannonia. The Discourse Completion Test (DCT) developed by Hendriks (2002) was used as an instrument, containing different situations to which the participants had to respond. The linguistic and cultural background of the participants was identified using an online tool, namely the Language History Questionnaire. The participants responses were then recorded and transcribed. The direct and indirect levels of the requests were analyzed by categorizing the head act and the internal (syntactic and lexical) and external modifiers. The data showed that the participants generally used more indirect strategies in making requests (86.2% indirect, 13.8% direct), especially those from Indonesia. Participants from Pakistan were the most direct in making requests. Moreover, they used more external modifiers than other participants to compensate for their directness.